Pengaruh Citra Merek dan Religiusitas terhadap Loyalitas Pelanggan yang Dimediasi oleh Kepuasan Pelanggan Sabun Mandi Lifebuoy di Kota Cimahi - Sidiq, Muhamad Fazri; Triwahyu Putra, Hariyadi (Journal of Management and Bussines (JOMB), 2024)
This study examines the influence of brand image and religiosity on customer loyalty of Lifebuoy soap in Cimahi City with customer satisfaction as a mediating factor. Data were collected through questionnaires distributed to 120 Muslim respondents aged 15-63 years who had used Lifebuoy soap. Data analysis was carried out using the SPSS version 25 application and the Sobel test to test the validity and reliability of the instrument as well as descriptive analysis, classical assumptions, and multiple regression. The findings of the study indicate that brand image and religiosity have a significant positive effect on customer satisfaction. However, brand image does not have a significant effect on customer loyalty, while religiosity has a significant negative effect on loyalty. Customer satisfaction is proven to have a significant positive effect on loyalty and mediates the influence of brand image and religiosity on customer loyalty. The results of this study are expected to provide insight for companies in designing relevant strategies to increase customer loyalty of Lifebuoy soap. Keywords: Brand Image, Customer Satisfaction, Customer Loyalty, Religiosity